Compositional analysis of live fish import trade in India - C. G. Joshy; A. Suresh; Panda, S. K.; C. N. Ravishankar (Indian Journal of Fisheries, 2022)
The live fish import trade in India under the harmonised system (HS) code 0301 (HS-0301) increased exponentially in terms of import quantity and value during the period 2000-2019. India imported 1.32 t of live fish worth US $ 0.017 million in 2000, which increased to 653.27 t worth US $ 3.21 million in 2019. The import of both marine as well as freshwater ornamental fish was found to increase during the period 2013-2019. The major countries exporting marine and freshwater ornamental fish to India were Thailand, Indonesia, Malaysia, Singapore and Sri Lanka. The import of live trout and carp to India was found to be very less during the period 2000-2019. The majority of live fish import to India accounted in the subclass HS030199 since 2017, with 81.55, 91.86 and 74.03% of total live fish imported to India in 2017, 2018 and 2019, respectively. Bangladesh accounted 81.02, 87.84 and 83.11% of total import quantity and 0.74, 82.42 and 49.51% of total import value under the sub-head HS-030199 during 2017, 2018 and 2019, respectively. While import of live fish offers economic opportunities, it has the potential to bring biosecurity threats including fish pathogens to Indian waters. The economic trade-off is to be evaluated on a case to case basis supported with legal and institutional back-up. Enacting a comprehensive legal framework and creating quarantine facilities are critical in this direction. Keywords: Compositional analysis, HS-0301, Import, Ornamental fish, , Trade balance